GROCERY STORE MANAGEMENT SYSTEM WEBSITE - Vidya Maskar1,SimpalDorage2,Sakshi Mane2, Sanika Kulkarni2,Mansi Kodak2 (International Journal of Innovations in Engineering Research and Technology, 2022)
The purpose of Grocery Store Management System is to automate the existing manual systemby the help of computerized equipment and full-fledged computer software, full filling theirrequirements, so that their valuable data/information can be stored for a longer period of easyaccessing and manipulation of the same. The required software and hardware are easily availableand easy to work with. Grocery Shop Management System, as described above, can lead to error free, secure, reliable and fast management system. It can assist the user to concentrate on their other activities rather toconcentrate on the record keeping. Thus it will help organization in better utilization of resources.The organization can maintain computerized records without redundant entries. That means thatone need not be distracted by information that is not relevant, while being able to reach theinformation.The aim is to automate its existing manual system by the help of computerized equipments andfull-fledged computer software, fulfilling their requirements, so that their valuable data/information can be stored for a longer period with easy accessing and manipulation of thesame. Basically the project describes how to manage for good performance and better services forthe clients.